Rare objects [videorecording (DVD)] - Holmes, Katie, 1978-; Holmes, Katie, 1978-; Papadopoulos, Phaedon; Mayorga, Julia; Santiago, Saundra; Buckley, Candy; Vidrio, Giancarlo; Luke, Derek, 1974-; Cumming, Alan, 1965- (IFC Films, 2023)
It tells the story of a young woman who seeks to rebuild her life when she takes work at an antique store. She regains her confidence from the kind souls who own the shop until those from her traumatic past begin to resurface.